The effects of role stressors and emotional satisfaction on service quality: Moderating role of gender - Handrio Adhi Pradana; Hunik Sri Runing Sawitri (Jurnal Siasat Bisnis, 2015)
The objective of this research is to find out the effect of role ambiguity, role conflict, role overload,  and work-family conflict on emotional satisfaction, the effect of emotional satisfaction on service quality, and gender moderation on the effect of emotional satisfaction on service quality. This research was conducted in Dr. Moewardi General Hospital. The research design used in was survey research. The population of this research was all nurses of Dr. Moewardi General Hospital. The sample consisted of 106 nurses taken using purposive sampling technique. The independent variables were role ambiguity, role conflict, role overload, work-family conflict, and emotional satisfaction. The dependent variables were service quality and emotional satisfaction, while gender was a moderating variable. Methods of analyzing data used in this research were multiple regression, simple regression, and subgroup analysis before which the instrument tests were conducted including validity and reliability tests. A multiple regression examined the effect of role ambiguity, role conflict, role overload, and work-family conflict on emotional satisfaction. Simple regression examined the effect of emotional satisfaction on service quality and subgroup analysis examined the moderation of gender on the effect of emotional satisfaction on the service quality. The result of this research showed that: (1) Role ambiguity, role overload, and work-family conflict affected the emotional satisfaction significantly and negatively while the role conflict did not affect significantly the emotional satisfaction, (2) The emotional satisfaction affected positively the service quality, (3) Gender did not moderate significantly the effect of emotional satisfaction on service quality.